Fatores associados à duração do aleitamento materno e panorama das ações e políticas pró-aleitamento em países da América Latina - Lamounier, Danielle Mendonça Buiatti (2020)
Introduction: The most countries in Latin America and the Caribbean have undergone major demographic changes, which have influenced the development of infant feeding public policies aimed to protect and support the breastfeeding (BF). The duration of BF has increased significantly in most countries in Latin America and the Caribbean in recent decades. Breastfeeding practices are influenced by socioeconomic and cultural determinants, the organization of health services, maternity protection and other health policies. When pro-breastfeeding interventions occur properly and at various levels, breastfeeding practices can improve rapidly. Objectives: To analyze the duration of BF in Latin American countries and the factors associated with the duration of BF along with pro-breastfeeding actions and policies in these countries. Methods: Cross-sectional study with data from demographics and health surveys (DHS) carried out in Bolivia, Brazil, Colombia, Peru and Dominican Republic. Children under two years old were selected. Information about pro-breastfeeding actions and policies was extracted from the World Breastfeeding Trends Initiative (WBTi) tool. The tool was composed by 10 items that include pro-breastfeeding actions and policies, and the total score ranging from 0 to 100 points. Higher score means higher number of actions and policies implemented in the country. The duration of BF was expressed as median, defined by survival analysis using Kaplan Meier curves. Cox's regression model was applied to verify the association of exposure variables with the duration of BF, expressed by hazard ratio (HR) and 95% confidence intervals. The multilevel regression model was used in order to estimate the average effect of the WBTi tool on the duration of BF in the set of countries (pooled analysis), with adjustment of the individual variables, related to the mother-child binomial and sociodemographic variables. Results: The duration of BF increased significantly in all the countries analyzed over the years, with emphasis on Brazil (increase of 6 months), Colombia (increase of 5 months) and Peru (increase of 5 months). In the Dominican Republic, the increase was not significant (p = 0.162). For the group of countries, we found that mothers with more schooling (HR = 1.64; CI = 1.33; 2.01), mothers classified in the highest income quintile (HR = 1.69; CI = 1.51; 190 ) and mothers with a higher BMI (HR = 1.14; CI = 1.05; 1.23) were risk factors for shorter breastfeeding duration. Breastfeeding in the first hour of life (HR = 0.78; CI = 0.74; 0.82) contributed to increase the duration of breastfeeding. Regarding the score of the WBTi tool, we observed shorter durations of breastfeeding in countries that had a higher score, that is, in countries that have more pro-breastfeeding actions and policies (HR = 1.06; CI = 1.05; 1 , 07). Conclusion: All countries showed a significant increase in the duration of BF, with the exception of the Dominican Republic. More educated mothers, classified in the highest income fifths and overweight, breastfed for less time. Mothers who breastfed the infant in the first hour of life had a longer duration of BF. Higher scores from the WBTi tool did not result in a longer duration of BF.